ABNORMALITAS NILAI PEAK EXPIRATORY FLOW RATE DAN FAKTOR- FAKTOR YANG MEMPENGARUHINYA PADA PENJUAL KORAN DI PERSIMPANGAN LAMPU LALU LINTAS KOTA PEKANBARU - Handayani Handayani; Adrianison Adrianison; Ririn Ariesty (Jurnal Ilmu Lingkungan, 2011)
The newspaper-sellers are one of informal sector workers who are susceptible to suffer respiratorysystem diseases affected by traffic air pollutant’s exposure. This study was aimed to desribe theprevalence of abnormality of Peak Expiratory Flowmetry Rate (PEFR) value among newspaper-sellers at traffic-lights in Pekanbaru and factors which were influenced. The study was held usinganalytic cross sectional disaign among 108 newspaper-sellers at 14 points of traffic-lights inPekanbaru. Interviewed and pyhsical examanination were done to the respondents to excludesubjects whom having respiratory illness which might caused by other causes inspite of traffic airpollutan’s exposure. The level of SO2, NO2 and PM10 as traffic air pollutants at those traffic-lightshad been examined by an officer from Laboratorium Udara Bappedalda Kota Pekanbaru usingmulti gas detector and lighthouse handheld 3016 IAQ. The PEFR value was examined by usingmini peak flowmeter. There were only 25 respondents fulfilled inclusion and exclusion criteria. ThePEFR value was 327,2 + 81,3 litre/minute. The prevalence of abnormality PEFR value was 52%among respondents. There were not association between age (p 0,165), sex (p 0,645), smokinghabit (p 0,286), length of work (p 0,541) and duration of exposure in a day (p 0,55) to theprevalence of abnormality of PEFR value among the respondents.